Adolescent Risk Factors for Child Maltreatment - Thornberry, Terence P. (2013)
We investigate adolescent risk factors, measured at both early and late adolescence, for involvement in child maltreatment during adulthood. Comprehensive assessments of risk factors for maltreatment that use representative samples with longitudinal data are scarce and can inform multilevel prevention. We use data from the Rochester Youth Development Study, a longitudinal study begun in 1988 with a sample of 1,000 seventh and eighth graders. Participants have been interviewed 14 times and, at the last assessment (age 31), 80% were retained. Risk factors represent 10 developmental domains: area characteristics, family background/structure, parent stressors, exposure to family violence, parent-child relationships, education, peer relationships, adolescent stressors, antisocial behaviors, and precocious transitions to adulthood. Maltreatment is measured by substantiated reports from Child Protective Services records. Many individual risk factors (20 at early adolescence and 14 at later adolescence) are significantly, albeit moderately, predictive of maltreatment. Several developmental domains stand out, including family background/structure, education, antisocial behaviors, and precocious transitions. In addition, there is a pronounced impact of cumulative risk on the likelihood of maltreatment. For example, only 3% of the youth with no risk domains in their background at early adolescence were involved in later maltreatment, but for those with risk in 9 developmental domains the rate was 45%. Prevention programs targeting youth at high risk for engaging in maltreatment should begin during early adolescence when risk factors are already at play. These programs need to be comprehensive, capable of addressing the multiple and interwoven nature of risk that is associated with maltreatment.